2017
DOI: 10.1186/s13007-017-0209-z
|View full text |Cite
|
Sign up to set email alerts
|

A procedure for maize genotypes discrimination to drought by chlorophyll fluorescence imaging rapid light curves

Abstract: BackgroundPhotosynthesis can be roughly separated into biochemical and photochemical processes. Both are affected by drought and can be assessed by non-invasive standard methods. Gas exchange, which mainly assesses the first process, has well-defined protocols. It is considered a standard method for evaluation of plant responses to drought. Under such stress, assessment of photochemical apparatus by chlorophyll fluorescence needs improvement to become faster and reproducible, especially in growing plants under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Previously several studies have shown that Fusarium species is having the capacity to damage the PSII in different plants (Santini et al 2008;Bauriegel et al 2011). In the last decade, the prompt chlorophyll fluorescence measurement has established itself as a quick method to estimate the plant stress responses (de Sousa et al 2017;Kalaji et al 2018). OJIP transient curves have been developed as a signature for plant stress, and any deviation from its usual shape indicates some abnormalities of the photosystem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously several studies have shown that Fusarium species is having the capacity to damage the PSII in different plants (Santini et al 2008;Bauriegel et al 2011). In the last decade, the prompt chlorophyll fluorescence measurement has established itself as a quick method to estimate the plant stress responses (de Sousa et al 2017;Kalaji et al 2018). OJIP transient curves have been developed as a signature for plant stress, and any deviation from its usual shape indicates some abnormalities of the photosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll a fluorescence kinetics studies using portable devices known as fluorometers or Plant Stress Meters (PSM) is one of the finest methods to investigate the function of PSII and its reactions to changes in the environment and plant growth conditions (Kalaji et al 2011). In recent years, changes in ChlF patterns in response to several stress factors has been reported, such as, drought (Berger et al 2010;Živčák et al 2014;de Sousa et al 2017), low or high light (Bartak et al 2004;Kalaji et al 2012;Hazrati et al 2016), salinity (Zhang et al 2010;Kalaji et al 2011), temperature (Kalaji et al 2011;Brestič et al 2012;Botta 2013;Huang et al 2017) and herbicides (Balabanova et al 2016). Nevertheless, photosynthetic performances of different maize lines by exploiting multi-parametric fluorescence devices under inoculation with F. verticillioides have not yet been explored at all.…”
Section: Introductionmentioning
confidence: 99%
“…However, it also restricts CO 2 entry in the leaf, which may lead to the decrease of the photosynthesis rate [9] and a decrease in primary photochemical processes [10], which will inhibit plant growth and even reduce dry matter accumulation and yield [11]. Therefore, the measurement of photosynthetic performance is considered a standard technique for studies on drought stress, especially, the photosynthesis rate (A), stomata conductance (gs), and transpiration (E) have been determined to be the most used techniques to discriminate the plant responses to drought [12][13][14]. The measurement of chlorophyll fluorescence is another standard technique for drought studies.…”
mentioning
confidence: 99%
“…The effects of drought on maize have been extensively investigated. In general, drought was shown to induce the decrease of photosynthesis in maize leaves, and this decrease was caused by stomatal closure and the decrease of the maximum quantum efficiency of photosystem II [11,14,22,23]. Drought might also lead to a reduction in total biomass and fraction of crop dry matter allocated to the grain [24].…”
mentioning
confidence: 99%
“…Additionally, temperature and humidity conditions can produce substantial errors of gas exchange rates altering stomatal responses and VPD at the leaf-level 44,57 . Repeated saturating pulses under dynamic actinic light on the same leaf was considered to have negligible effects on fluorescence measurements as duration between pulses was longer (i.e., every 30 seconds) than rapid light fluorescence curves measurements (e.g., 0.8–10 seconds) 58,59 . Nevertheless, Ψ L and time point fluorescence measurements were taken under direct influence of the spectral variations of the eclipse and were not significantly different from chamber observations (Fig.…”
Section: Discussionmentioning
confidence: 99%